A blended learning programme on hand-knitted goods - Alsarhan, Thanaa Mustafa Aref; Saroukh, Safia Abdelaziz Kotb (Journal of Humanities & Social Sciences, 2018)
This study aimed to reveal the effectiveness of a blended learning (BL) programme in a tertiary-level hand-knitted goods course. The sub-objectives were: (1) To compare the effectiveness of a traditional learning programme and a BL programme in terms of the development of hand-knitting knowledge and skills, and (2) To study the differences in students’ skill performance levels between the two programmes, design: The study was conducted in the laboratories of the Fashion Design Department at Abdulaziz University in Saudi Arabia with 21 student participants. The research tools comprised (1) a questionnaire and (2) a skilled performance observation card to assess the production of hand-knitted goods before and after the application of each learning method. Findings: The results demonstrated significant differences in favour of the BL method (p = .01) between the average skilled performance evaluations of students’ production of hand-knitted goods for each of the two methods. Originality/Value: This study contributes to the improvement of learning outputs and increases the effectiveness of the educational process by applying the BL method in different fields of clothing largely based on skilled performance.
Keywords: programme; traditional learning; blended learning; hand knitting